Implementasi Kurikulum Merdeka dalam Pembentukan Karakter Peduli Lingkungan Peserta Didik di MAN 1 Pangandaran - Hani Pitriani (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
This research aims to analyze the implementation of the independent curriculum in shaping the environmental caring character of students at MAN 1 Pangandaran through the strengthening project of Pancasila student profiles (P5). This study uses qualitative methods, with subjects consisting of the school principal, vice principal for curriculum, P5 coordinator, and students. The research was conducted at MAN 1 Pangandaran. Data collection techniques used in this study include observation, interviews, and documentation conducted directly in the field. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. The results of the study can be concluded that the implementation of the independent curriculum through P5 in shaping the environmental caring character is well implemented. The implementation process goes through three stages: interpretation, organization, and application. Interpretation is carried out with mutual understanding among all parties.